Preparation method of near-infrared laser sensitive composite energetic material
By generating nanosilver and photoconductive polymers on HMX crystals, combining electrolytes to increase the electrolyte concentration of the system, the problem of low sensitivity of HMX and CL-20 to near-infrared lasers is solved, and efficient laser ignition performance and reduced mechanical sensitivity are achieved. Effect.
Patent Information
- Application Number
- CN202411263730.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-10
AI Technical Summary
Existing high-energy density nitroamine explosives such as HMX and CL-20 have low sensitivity to near-infrared lasers and are difficult to cause ignition by lasers. In addition, the nanometal doped methods have problems such as high cost, uneven distribution and improved mechanical sensitivity.
By reacting silver nitrate and orthophenyldiamine with recrystallized HMX crystals in a solid-liquid system, nanosilver and photosensitive conductive polymer polyophenyldiamine were generated. The nanosilver particles were grown on the surface of HMX using in situ growth technology. , combining sodium chloride or sodium nitrate to increase the electrolyte concentration and improve the near-infrared laser sensitivity and ignition performance of the composite material.
It significantly reduces the ignition energy threshold and delay time, improves the near-infrared laser sensitivity, improves the laser ignition performance, and reduces the mechanical sensitivity. It is suitable for use in high safety and high energy density laser ignition systems for energy-containing materials.
Smart Images

Figure CN119118758A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of laser photosensitive composite energetic materials, and in particular relates to a method for preparing a near-infrared laser-sensitive composite energetic material. Background Art
[0002] The development of high-safety, high-energy insensitive ammunition is an urgent requirement and key demand in the current energetic material field. The laser ignition technology of energetic materials is one of the important ways to solve the safety of ammunition. The energetic material laser ignition system requires that the agent used is a laser-sensitive, insensitive high-energy explosive. Therefore, the laser ignition of high-energy density nitramine explosives represented by Octogen (HMX) and CL-20 has attracted attention. The laser ignition of energetic materials is based on the interaction between lasers of a certain wavelength and energetic materials. Its mechanism includes photochemical, photothermal, photoelectric, and photopressing effects. Studies have shown that nitramine explosive crystals such as HMX and CL-20 have strong absorption in the ultraviolet band, but basically have no absorption for near-infrared lasers with wavelengths greater than 800nm, and are difficult to be ignited by near-infrared lasers. However, ultraviolet lasers are large in size, expensive, and not suitable for laser ignition systems; the working wavelengths of small and cheap semiconductor diode lasers are mostly in the near-infrared region with wavelengths greater than 800nm. Therefore, it is necessary to improve the near-infrared laser sensitivity of nitramine explosive crystals such as HMX and CL-20, while reducing the mechanical sensitivity to achieve laser ignition, thereby meeting the needs of energetic material laser ignition systems.
[0003] The main way to improve the near-infrared laser sensitivity of nitramine explosive crystals such as HMX and CL-20 is to add or dope photosensitive substances, and carbon materials, dyes, nanometals, etc. have been reported. Among them, the carbon materials used include carbon black, graphite, oxidized / reduced graphene, C nanotubes, etc. Carbon black has the best laser sensitization effect, which can reduce the ignition energy threshold and shorten the ignition delay time. However, carbon black is prone to self-agglomeration, which affects the uniform distribution in the reagent, and then affects the continuity of ignition and fire transmission; nanometals include Au, Ti, Ni, Cu, Mg, Al, etc., which utilize the good electrical conductivity, thermal conductivity, optics, surface free electron plasma resonance effect and other optical properties and photothermal conversion performance of metal nanoparticles, and are prepared by non-solvent suspension-recrystallization method, grinding mixing method, ultrasonic suspension method and other methods, and are doped on the surface or inside of explosive crystals. The applicable ignition wavelengths are different, and they can reduce the ignition threshold and shorten the delay time to a certain extent. However, there are still problems such as uneven doping, cracks in explosive crystals, easy oxidation, or high cost and unsuitable for practical application, and easy migration between explosive crystal particles by electrostatic adsorption. However, doping nanometals to increase the laser sensitivity of explosive crystals has advantages. In-depth research is still needed from the aspects of preparation methods, composite mechanisms, laser ignition mechanisms, and comprehensive mechanical sensitivity and thermal sensitivity properties to promote practical applications. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to achieve these objects and other advantages according to the present invention, there is provided a method for preparing a near-infrared laser-sensitive composite energetic material, comprising a positive addition method:
[0006] Step 1: First, industrial octogen (HMX) is recrystallized to obtain recrystallized octogen (HMX R ) crystals for later use, o-phenylenediamine (oPD) was dissolved in ultrasonically deoxygenated deionized water at room temperature to obtain o-phenylenediamine solution I, and then HMX R The crystals are added to o-phenylenediamine solution I to form a suspension system A;
[0007] Step 2: dissolving silver nitrate in ultrasonically deoxygenated deionized water at room temperature to prepare a silver nitrate solution I, and adding the silver nitrate solution I dropwise into the system A at a certain rate, and continuing to stir the reaction after the addition is complete;
[0008] Step 3: After the reaction is completed, the mixture is filtered and washed with deionized water for multiple times, and then the filter cake is dried in a vacuum drying oven to obtain a composite energetic material.
[0009] Preferably, the step 1 and the step 2 are adjusted to be the reverse addition method:
[0010] S1. First, industrial octogenin (HMX) is recrystallized to obtain recrystallized octogenin (HMX R ) crystals for later use, silver nitrate was dissolved in ultrasonically deoxygenated deionized water at room temperature to prepare silver nitrate solution II, and then HMX R The crystals are added to silver nitrate solution II to form suspension system B;
[0011] S2, at room temperature, o-phenylenediamine is dissolved in ultrasonically deoxygenated deionized water to obtain o-phenylenediamine solution II, and o-phenylenediamine solution II is added dropwise to system B at a certain rate, and the reaction is continued by stirring after the addition is completed;
[0012] S3. After the reaction is completed, the mixture is filtered and washed with an appropriate amount of deionized water for multiple times. The filter cake is then dried in a vacuum drying oven to obtain a composite energetic material.
[0013] Preferably, in step 1, the concentration of the prepared o-phenylenediamine solution I is 0.0020-0.0300 g / mL, and o-phenylenediamine and HMX R The mass ratio of the crystals is 0.03-0.35:1, and the stirring time is 0.5-6h.
[0014] Preferably, in step 2, the concentration of the silver nitrate solution I is 0.002-0.008 g / mL, and the silver nitrate and HMX R The mass ratio of the crystals is 0.03-0.15:1, and the acceleration rate of one drop of the silver nitrate solution is 0.1-1.0 mL / min, and the stirring reaction is performed for 4-24 hours.
[0015] Preferably, in step three, the drying temperature is 45 to 60° C., and the drying time is 10 to 24 hours.
[0016] Preferably, in said S1, the concentration of the prepared silver nitrate solution II is 0.002-0.008 g / mL, and the silver nitrate and HMX R The mass ratio of the crystal is 0.03 to 0.15:1.
[0017] Preferably, in S2, the concentration of o-phenylenediamine solution II is 0.0030-0.0300 g / mL, and o-phenylenediamine and HMX R The mass ratio of the crystals is 0.03-0.35:1, the dropping rate of the o-phenylenediamine solution II is 0.1-1.0 mL / min, and the reaction is stirred for 4-24 hours.
[0018] Preferably, in S3, the drying temperature is 45 to 60° C., and the drying time is 10 to 24 hours.
[0019] Preferably, the positive addition method is improved by adding sodium chloride or sodium nitrate to the mixed system after step 2 in an amount of HMX R 0.1-1wt% of the crystals, continue stirring the reaction for 2-6h.
[0020] Preferably, the reverse addition method is improved by adding sodium chloride or sodium nitrate to the mixed system after S2 in an amount of HMX R 0.1-1wt% of the crystals, continue stirring the reaction for 2-6h.
[0021] The present invention has at least the following beneficial effects:
[0022] (1) Using silver nitrate (AgNO3), o-phenylenediamine (oPD) and octogenol (HMX) as raw materials, silver ions and o-phenylenediamine undergo redox reactions to generate nano-elemental silver and o-phenylenediamine oligomers, which are then further polymerized to generate poly-o-phenylenediamine (PoPD). Nano-silver and photosensitive conductive polymer poly-o-phenylenediamine are used to synergistically increase near-infrared laser sensitivity. Nano-silver is cheaper than nano-gold and easier to prepare than other nano-metals such as Au, Ti, Ni, Cu, Mg, and Al.
[0023] (2) Using in-situ growth technology in a solid-liquid system at room temperature, the silver nanoparticles are grown on the recrystallized HMX R The crystal surface has strong interface interaction, and the nanosilver particles are not easy to be R Surface detachment;
[0024] (3) In this preparation system, nanosilver and poly(o-phenylenediamine) (PoPD) grow in the same system. R Poly(o-phenylenediamine) adsorbed on HMX / Ag / PoPD composite energetic materials R Particle surface or filled with HMX R Between particles, it increases photosensitivity and reduces mechanical sensitivity, improving the laser ignition performance of composite energetic materials;
[0025] (4) Preparation of HMX by in situ growth technique in solid-liquid system at room temperature R / Ag / PoPD composite photosensitive energetic material, by adding a small amount of sodium chloride or sodium nitrate to increase the electrolyte concentration in the system, so as to increase the product's absorption of near-infrared laser, thereby improving the near-infrared laser sensitivity and the product's laser ignition performance. The reaction conditions are mild, easy to operate, safe, and energy-saving;
[0026] (5) The technical solution adopted by the present invention can be extended to the design and preparation of non-water-soluble energetic matrix photosensitive composite energetic materials such as RDX and CL-20, and can be improved in the structure and type of photosensitive conductive polymers, such as adding hydroxyl groups to make it have a stronger adsorption force with the HMX crystal surface so that the two can be more closely combined, or making it have stronger near-infrared absorption.
[0027] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a flow chart of the positive addition method of the present invention;
[0029] Figure 2 It is a flow chart of the reverse addition method of the present invention;
[0030] Figure 3 HMX in Example 1 of the present invention R SEM image before compounding;
[0031] Figure 4 This is a SEM image of the composite energetic material obtained in Comparative Example 1 of the present invention;
[0032] Figure 5 This is a SEM image of the composite energetic material obtained in Example 2 of the present invention;
[0033] Figure 6 This is a SEM image of the composite energetic material obtained in Example 1 of the present invention;
[0034] Figure 7 This is a SEM image of the composite energetic material obtained in Example 3 of the present invention;
[0035] Figure 8 This is a SEM image of the composite energetic material obtained in Example 4 of the present invention;
[0036] Fig. 9 This is a SEM image of the composite energetic material obtained in Example 5 of the present invention;
[0037] Fig.10 This is a SEM image of the composite energetic material obtained in Example 6 of the present invention;
[0038] Fig.11 This is a SEM image of the composite energetic material obtained in Example 7 of the present invention;
[0039] Fig.12 This is a SEM image of the composite energetic material obtained in Example 8 of the present invention;
[0040] Fig.13 The PXRD diagram of the composite energetic material obtained before HMX compounding in Example 1 of the present invention and Examples 1, 3 to 5 and Comparative Example 1;
[0041] Fig.14 This is a graph showing the test results of the laser ignition performance of the composite energetic material obtained in Examples 1, 3 to 5 of the present invention. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0043] Example 1
[0044] A method for preparing a near-infrared laser-sensitive composite energetic material, which is prepared by a positive addition method in this embodiment:
[0045] Step 1: First, industrial octogen (HMX) is recrystallized to obtain recrystallized octogen (HMX R ) crystals for later use, add 10 mL of deionized water to a flask at room temperature, add a magnet, ultrasonicate for 15 min to drive out O2, add 0.0400 g of o-phenylenediamine (oPD), ultrasonicate for about 30 min to dissolve oPD, and obtain oPD solution I; add 0.9800 g of recrystallized octogen (HMX R , the SEM picture is attached Figure 3), and magnetically stirred at room temperature for 2 h to obtain suspension system A;
[0046] Step 2: Take 10 mL of deionized water at room temperature and add it to a beaker. Add a magnet and drive off O2 by ultrasonication for 15 min. Then, add 0.0315 g of AgNO3 (wherein the Ag content is 0.0200 g) and dissolve it to obtain AgNO3 solution I. Add the prepared AgNO3 solution I dropwise into the suspension system A at a rate of 0.5 mL / min at 25 ° C. After complete addition, continue stirring and reacting for 8 h.
[0047] Step 3: After the reaction is completed, filter and wash the precipitate with appropriate amount of deionized water for several times, then dry the filter cake in a vacuum drying oven at 45°C for 24 hours to obtain HMX R / Ag / PoPD composite energetic material, marked as A-2%Ag.
[0048] Example 2
[0049] A method for preparing a near-infrared laser-sensitive composite energetic material, which is prepared by a reverse addition method in this embodiment:
[0050] S1. First, industrial octogenin (HMX) is recrystallized to obtain recrystallized octogenin (HMX R ) crystals for later use, add 10 mL of deionized water to a 50 mL flask at room temperature, add a magnet, sonicate for 15 min, add 0.0315 g of AgNO3 (wherein the Ag content is 0.0200 g), dissolve, and prepare AgNO3 solution II, to which 0.9800 g of HMX R , magnetically stirred at room temperature for 2 h to obtain suspension system B;
[0051] S2. Take 10 mL of deionized water at room temperature and ultrasonicate for 15 min, add 0.0800 g of oPD, and ultrasonicate for 30 min to dissolve the oPD to obtain oPD solution II; add oPD solution II dropwise into suspension system B at a rate of 0.5 mL / min. After complete addition, continue stirring and reacting for 8 h;
[0052] S3. After the reaction is completed, the precipitate is filtered and washed with an appropriate amount of deionized water for several times, and then the filter cake is dried in a vacuum drying oven at 45°C for 24 hours to obtain HMX R / Ag / PoPD composite energetic material, marked as B-2%Ag.
[0053] Example 3
[0054] The difference between this embodiment and embodiment 1 is that the amount of o-phenylenediamine (oPD) added is 0.1200 g, and HMX RThe amount of addition was 0.9700 g, the amount of AgNO3 used was 0.0471 g, and the other steps were consistent with Example 1, and finally HMX marked as A-3% Ag was obtained. R / Ag / PoPD composite energetic materials.
[0055] Example 4
[0056] The difference between this embodiment and embodiment 1 is that the amount of o-phenylenediamine (oPD) added is 0.1600 g, and HMX R The amount of addition was 0.9600 g, the amount of AgNO3 used was 0.0628 g, and the other steps were consistent with Example 1, and finally HMX marked as A-4% Ag was obtained. R / Ag / PoPD composite energetic materials.
[0057] Example 5
[0058] The difference between this embodiment and embodiment 1 is that the amount of o-phenylenediamine (oPD) added is 0.2000 g, and HMX R The amount of addition was 0.9500 g, the amount of AgNO3 used was 0.0785 g, and the other steps were consistent with Example 1, and finally HMX marked as A-5% Ag was obtained. R / Ag / PoPD composite energetic materials.
[0059] Example 6
[0060] The difference between this embodiment and embodiment 2 is that the amount of AgNO3 added is 0.0471 g, and the amount of HMX R The addition amount was 0.9700 g, the amount of o-phenylenediamine (oPD) was 0.1200 g, and the other steps were consistent with Example 2, and finally HMX marked as B-3% Ag was obtained. R / Ag / PoPD composite energetic materials.
[0061] Example 7
[0062] The difference between this embodiment and embodiment 2 is that the amount of AgNO3 added is 0.0628 g, and the amount of HMX R The addition amount was 0.9600 g, the amount of o-phenylenediamine (oPD) was 0.1600 g, and the other steps were consistent with Example 2, and finally HMX marked as B-4% Ag was obtained. R / Ag / PoPD composite energetic materials.
[0063] Example 8
[0064] The difference between this embodiment and embodiment 2 is that the amount of AgNO3 added is 0.0785 g, and the amount of HMX RThe addition amount was 0.9500 g, the amount of o-phenylenediamine (oPD) was 0.2000 g, and the other steps were consistent with Example 2, and finally HMX marked as B-5% Ag was obtained. R / Ag / PoPD composite energetic materials.
[0065] Example 9
[0066] The difference between this embodiment and embodiment 5 is that after step 2, 0.0050 g of sodium chloride is added to the mixed system, and the stirring reaction is continued for 4 hours.
[0067] The remaining steps are consistent with Example 5.
[0068] Example 10
[0069] The difference between this embodiment and embodiment 8 is that after step 2, 0.0050 g of sodium chloride is added to the mixed system, and the stirring reaction is continued for 4 hours.
[0070] The remaining steps are consistent with Example 8.
[0071] Comparative Example 1
[0072] A method for preparing a near-infrared laser-sensitive composite energetic material, which is prepared by a positive addition method in this embodiment:
[0073] Step 1: First, industrial octogen (HMX) is recrystallized to obtain recrystallized octogen (HMX R ) crystals for later use, add 10 mL of deionized water to a flask at room temperature, add a magnet, ultrasonicate for 15 min to drive out O2, add 0.0400 g of o-phenylenediamine (oPD), ultrasonicate for about 30 min to dissolve oPD, and obtain oPD solution I; add 0.9900 g of recrystallized octogen (HMX R , the SEM picture is attached Figure 3 ), and magnetically stirred at room temperature for 2 h to obtain suspension system A;
[0074] Step 2: Take 10 mL of deionized water at room temperature and add it to a beaker. Add a magnet and drive off O2 by ultrasonication for 15 min. Then, add 0.0157 g of AgNO3 (wherein the Ag content is 0.0100 g) and dissolve it to obtain AgNO3 solution I. Add the prepared AgNO3 solution I dropwise into the suspension system A at a rate of 0.5 mL / min at 25°C. After complete addition, continue stirring and reacting for 8 h.
[0075] Step 3: After the reaction is completed, filter and wash the precipitate with appropriate amount of deionized water for several times, then dry the filter cake in a vacuum drying oven at 45°C for 24 hours to obtain HMX R / Ag / PoPD composite energetic material, marked as A-1%Ag.
[0076] Comparative Example 2
[0077] Step 1: Add 10 mL of deionized water to a flask at room temperature, add a magnet, and ultrasonicate for 15 minutes to drive out O2, then add 0.0400 g of o-phenylenediamine (oPD), and ultrasonicate for about 30 minutes to dissolve oPD to obtain oPD solution I; add 0.9900 g of industrial octogenin (HMX) to oPD solution I, and magnetically stir at room temperature for 2 hours to obtain suspension system A;
[0078] Step 2: Take 10 mL of deionized water at room temperature and add it to a beaker. Add a magnet and drive off O2 by ultrasonication for 15 min. Then, add 0.0315 g of AgNO3 (wherein the Ag content is 0.0200 g) and dissolve it to obtain AgNO3 solution I. Add the prepared AgNO3 solution I dropwise into the suspension system A at a rate of 0.5 mL / min at 25 ° C. After complete addition, continue stirring and reacting for 8 h.
[0079] Step 3: After the reaction is completed, the mixture is filtered and washed with an appropriate amount of deionized water for multiple times. The filter cake is then dried in a vacuum drying oven at 45° C. for 24 h to obtain a HMX / Ag / PoPD composite energetic material.
[0080] Comparative Example 3
[0081] The only difference from Example 1 is that the deionized water containing oPD and AgNO3 is not subjected to ultrasonic oxygen removal. The obtained product is silver-grey and does not contain PoPD.
[0082] Comparative Example 4
[0083] The only difference from Example 1 is that AgNO3 solution I is added dropwise to suspension system A at a rate of about 2.0 mL / min. The generated elemental silver is mainly accumulated on the wall of the reaction flask in the form of a silver mirror. The product obtained is brown-yellow HMX R / PoPD composite energetic materials.
[0084] The composite energetic materials obtained in Examples 1 to 10 and Comparative Examples 1 to 4 were characterized in morphology and structure, and the mechanical sensitivity and laser ignition performance of the samples were tested. Laser ignition tests were carried out on the composite energetic materials with different Ag contents using a laser and high-speed photography. The ignition conditions were: room temperature, normal pressure, open environment, laser wavelength of 1064 nm, pulse width of 110 μs, pulse repetition frequency of 10 Hz, spot diameter of approximately 2 mm, total laser stroke of 175 mm, and lens focal length of 200 mm.
[0085] The impact sensitivity and friction sensitivity of the prepared composite energetic material were tested according to method 601.1 impact sensitivity (explosion probability method) and 601.2 friction sensitivity (explosion probability method) in GJB 772A-97 "Test Methods for Explosives". The mechanical sensitivity test results are shown in Table 1.
[0086] Table 1HMX R And the mechanical sensitivity test results of composite energetic materials with different Ag contents
[0087]
[0088] It can be seen from Table 1 that HMX with different silver contents R The impact sensitivity of the / Ag / PoPD composite energetic material is lower than 20%, and the friction sensitivity gradually decreases with the increase of silver content. For example, in Example 4, when the Ag content is 4%, the friction sensitivity of the composite energetic material drops to 48%, which is lower than that of the recrystallized HMX R The friction sensitivity of the HMX prepared by the method of the present invention is reduced by 40%. R / Ag / PoPD composite energetic materials can significantly improve the mechanical sensitivity performance. Compared with the positive addition method, the impact sensitivity and friction sensitivity of the reverse addition method are generally lower, which shows that the reverse addition method can better improve the HMX R / Ag / PoPD composite energetic material mechanical sensitivity. In Comparative Example 1, due to the small amount of added silver, the friction sensitivity of the energetic material finally obtained is still relatively high. In Comparative Example 2, due to the use of HMX crystals that have not been recrystallized to prepare the composite energetic material, its impact sensitivity is still relatively high. In Comparative Example 3, the deionized water in which oPD and AgNO3 are dissolved is not subjected to ultrasonic oxygen removal, resulting in the inability of oPD to polymerize to generate PoPD, and the friction sensitivity of the final product is still relatively high. In Comparative Example 4, the generated elemental silver is mainly gathered on the wall of the reaction bottle in the form of a silver mirror, and does not grow in the energetic material, and its friction sensitivity is still relatively high.
[0089] from Figure 6 to Figure 9 It can be seen that in the composite energetic material sample prepared by the positive addition method, the gem-like HMX R Silver nanoparticles and linear PoPD are distributed on the crystal surface. As the silver content increases, the number of nanoparticles on the crystal surface increases, and some PoPD is scattered on the HMX R Between crystal particles. Figure 5 , Figure 10 to Figure 12 It can be seen that Figure 6 to Figure 9 Similarly, in the composite energetic material samples prepared by the reverse addition method, gem-like HMX R Silver nanoparticles and linear PoPD are distributed on the crystal surface. As the silver content increases, the number of nanoparticles on the crystal surface increases, and some PoPD is scattered on the HMX RBetween crystal particles, compared with the positive addition product, the HMX in the reverse addition product sample R Slightly more PoPD lines are attached to the crystal surface, which can better improve HMX R The mechanical sensitivity of Ag / PoPD composite energetic materials. The good ductility and thermal conductivity of silver nanoparticles and the flexibility of polymer PoPD contribute to the improvement of the mechanical sensitivity of composite energetic materials. Their respective photoelectric and photothermal properties play a decisive role in improving the photosensitivity of composite energetic materials.
[0090] from Fig.13 It can be seen that the main diffraction peaks in the PXRD spectra of composite energetic materials with different silver contents are similar to those of HMX R There are slight diffraction peaks with the same position peak diffraction angles as those in the standard card Ag (PDF#87-0597) and PoPD (PDF#31-1837), indicating that the HMX crystal form in the composite energetic materials with different silver contents is different from HMX R The composite energetic material contains Ag and PoPD. This proves that the composite energetic material was successfully prepared and maintained stable HMX R Crystal form.
[0091] from Fig.14 It can be seen that, taking the laser ignition of samples A-2% to A-5% as an example, the composite energetic materials with a silver content of 2% to 5% can achieve good ignition under the same 1064nm laser energy, while the composite energetic materials with a silver content of 1% in Comparative Example 1 cannot achieve good self-sustaining combustion, which is not listed here. As the silver content increases, the brightness of the single strongest flame increases and the volume increases, indicating that as the silver content and PoPD content increase, the utilization rate of the composite energetic material for laser energy increases, and the number of hot spots generated per unit time increases, which effectively promotes ignition and combustion. In Examples 9 and 10, a small amount of sodium chloride is added to increase the electrolyte concentration in the system, thereby promoting the further polymerization of the o-phenylenediamine oligomer in the solution in the later stage of the reaction into poly-o-phenylenediamine, increasing the content of PoPD in the product and its degree of polymerization to a certain extent, improving the utilization rate of the raw material oPD, and increasing the absorbance of the product to near-infrared laser, thereby improving the sensitivity of near-infrared laser and improving the laser ignition performance of the product.
[0092] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a near-infrared laser-sensitive composite energetic material, characterized in that: Including positive addition: Step 1: firstly, industrial octogenin is recrystallized to obtain recrystallized octogenin crystals for standby use; o-phenylenediamine is dissolved in ultrasonically deoxygenated deionized water at room temperature to obtain o-phenylenediamine solution I; and then, under stirring, the recrystallized octogenin crystals are added to the o-phenylenediamine solution I to form a suspension system A; Step 2: dissolving silver nitrate in ultrasonically deoxygenated deionized water at room temperature to prepare a silver nitrate solution I, and adding the silver nitrate solution I dropwise into the system A at a certain rate, and continuing to stir the reaction after the addition is complete; Step 3: After the reaction is completed, the mixture is filtered and washed with deionized water for multiple times, and then the filter cake is dried in a vacuum drying oven to obtain a composite energetic material.
2. The method for preparing a near-infrared laser-sensitive composite energetic material according to claim 1, characterized in that: Adjust the steps 1 and 2 to achieve the reverse addition method: S1. First, industrial octogenin is recrystallized to obtain recrystallized octogenin crystals for standby use. Silver nitrate is dissolved in ultrasonically deoxygenated deionized water at room temperature to obtain a silver nitrate solution II. Then, the recrystallized octogenin crystals are added to the silver nitrate solution II under stirring to form a suspension system B. S2, at room temperature, o-phenylenediamine is dissolved in ultrasonically deoxygenated deionized water to obtain o-phenylenediamine solution II, and o-phenylenediamine solution II is added dropwise to system B at a certain rate, and the reaction is continued by stirring after the addition is completed; S3. After the reaction is completed, the mixture is filtered and washed with an appropriate amount of deionized water for multiple times. The filter cake is then dried in a vacuum drying oven to obtain a composite energetic material.
3. The method for preparing a near-infrared laser-sensitive composite energetic material according to claim 1, characterized in that: In the step 1, the concentration of the prepared o-phenylenediamine solution I is 0.0020-0.0300 g / mL, the mass ratio of o-phenylenediamine to recrystallized octogen crystals is 0.03-0.35:1, and the stirring time is 0.5-6 h.
4. The method for preparing a near-infrared laser-sensitive composite energetic material according to claim 1, characterized in that: In the step 2, the concentration of the silver nitrate solution I is 0.002-0.008 g / mL, the mass ratio of silver nitrate to recrystallized octogen crystals is 0.03-0.15:1, the acceleration rate of the silver nitrate solution I drop is 0.1-1.0 mL / min, and the reaction is stirred for 4-24 hours.
5. The method for preparing a near-infrared laser-sensitive composite energetic material according to claim 1, characterized in that: In the step 3, the drying temperature is 45 to 60° C. and the drying time is 10 to 24 hours.
6. The method for preparing a near-infrared laser-sensitive composite energetic material according to claim 2, characterized in that: In S1, the concentration of the prepared silver nitrate solution II is 0.002-0.008 g / mL, and the mass ratio of silver nitrate to recrystallized octogen crystals is 0.03-0.15:
1.
7. The method for preparing a near-infrared laser-sensitive composite energetic material according to claim 2, characterized in that: In S2, the concentration of o-phenylenediamine solution II is 0.0020-0.0300 g / mL, the mass ratio of o-phenylenediamine to recrystallized octogen crystals is 0.03-0.35:1, the dropping rate of o-phenylenediamine solution II is 0.1-1.0 mL / min, and the reaction is stirred for 4-24 hours.
8. The method for preparing a near-infrared laser-sensitive composite energetic material according to claim 2, characterized in that: In S3, the drying temperature is 45 to 60° C., and the drying time is 10 to 24 hours.
9. The method for preparing a near-infrared laser-sensitive composite energetic material according to claim 1, characterized in that: The positive addition method is improved by adding sodium chloride or sodium nitrate to the mixed system after step 2, and the added amount is HMX R 0.1-1wt% of the crystals, continue stirring the reaction for 2-6h.
10. The method for preparing a near-infrared laser-sensitive composite energetic material according to claim 2, characterized in that: The reverse addition method is improved by adding sodium chloride or sodium nitrate to the mixed system after S2 in an amount of HMX R 0.1-1wt% of the crystals, continue stirring the reaction for 2-6h.
Citation Information
Patent Citations
Silver@polyaniline nano composite for photothermal therapy and preparation method thereof
CN106362150A
Preparation method of laser induced mono-disperse Ag-Ag2S nano-particle photocatalyst
CN106475038A
Recovery of the energetic component from plastic bonded explosives
US20060070690A1
Nanoparticles, Compositions, Manufacture and Applications
US20140227548A1
Methods of fabricating laser-induced graphene and compositions thereof
US20190330064A1
